FAKTOR DETERMINAN KASUS Open Defecation Free (ODF) DI DESA DINGIL KECAMATAN JATIROGO KABUPATEN TUBAN TAHUN 2020 - Hasanah, Uswatun; ., Winarko; Suryono, Hadi (Jurnal Higiene Sanitasi, 2022)
A family latrine is a building that is used to dispose of human feces or najis for a family which is commonly called a latrine or WC. For houses that do not have latrines, it is certain that they will use rice fields, rivers, gardens, ponds, or other places to defecate. Dingil Village in Jatirogo District has 1,011 houses with the highest number of Open Defecation (OD) namely 199 houses (20%) still open defecation, 812 houses have access to healthy latrines. The purpose of this study was to determine the determinant factors associated with the high number of OD in Dingil Village, Jatirogo District, Tuban Regency. This study uses an analytical method with a case control approach. Data was collected by interview and observation using a questionnaire sheet and instruments. The population in this study was 199 houses consisting of 66 people defecating (case group) and 66 people defecating in the toilet (as control). The data obtained were then analyzed using the Odds Ratio. The results showed that the aspects of knowledge, attitude and availability of good clean water turned out to be more than 65% of the community still defecating in any place, except for the type of good latrine, only 18.2% were open defecation. Knowledge, attitude and availability of clean water are not determinants of the high number of OD, except the type of latrine is a determinant factor of the high number of OD. It is recommended that the community no longer use rice fields, rivers, swamps for open defecation, share with family members whose houses are close together and apply a clean and healthy lifestyle to create an environment free of dirt/feces.